2018
DOI: 10.1159/000488252
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and Vascular Endothelial Growth Factor Receptor-Tyrosine Kinase Inhibitors in Renal Cancer

Abstract: Treatment of metastatic renal cell carcinoma (mRCC) has seen substantial progress over the last decade. A number of targeted therapies have been shown to improve clinical outcome. Vascular endothelial growth factor receptor (VEGFR)-tyrosine kinase inhibitors (TKIs) are an effective option in treating mRCC. RCC is traditionally perceived to be a radioresistant malignancy with a limited role of radiotherapy (RT) in the management of localized disease. While RCC appears to be radioresistant using conventionally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As discussed earlier, the mechanism of action of several chemotherapeutic agents is through increased ROS production and elevated oxidative stress in cancer cells 12 . Sorafenib is a multikinase inhibitor, which can downregulate tumor proliferation and angiogenesis 21,22 . Sorafenib is currently being used in the treatment for metastatic RCC and other cancers 2123 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, the mechanism of action of several chemotherapeutic agents is through increased ROS production and elevated oxidative stress in cancer cells 12 . Sorafenib is a multikinase inhibitor, which can downregulate tumor proliferation and angiogenesis 21,22 . Sorafenib is currently being used in the treatment for metastatic RCC and other cancers 2123 .…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib is a multikinase inhibitor, which can downregulate tumor proliferation and angiogenesis 21,22 . Sorafenib is currently being used in the treatment for metastatic RCC and other cancers 2123 . Sorafenib is known to generate ROS and inhibit mitochondrial respiration along with the interruption of cellular glycolysis 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, receptor tyrosine kinase (RTK) inhibitor family molecules have been used for the therapy of multiple cancers, including lung cancer [36], renal cancer [37], and cholangiocarcinoma [38]. Interestingly, our previous study found that the receptor tyrosine kinase (RTK) inhibitor brivanib downregulates the phosphorylation of FGFR1 and…”
Section: Discussionmentioning
confidence: 99%
“…Many other molecules are being developed. Advances in metastatic RCC have markedly increased with such medications [1][2][3][4][5].…”
mentioning
confidence: 99%
“…Although RCC is a tumor that is resistant to conventional RT. In preclinical studies, RCC has been reported to show higher radio sensitivity when using a program subject to ablative, hypo fraction in RT [5][6][7]. There are currently no phase 2 and 3 studies evaluating this combination in the literature.…”
mentioning
confidence: 99%